PREVALENCE OF FAMILY PLANNING METHODS AMONG MARRIED WOMEN AT THQ HOSPITAL SHABQADAR CHARSADDA KPK PAKISTAN (The Research of Medical Science Review, 2025)
Background: Developing countries are facing rapid growth of papulation due to different reasons such as high fertility rate. Different methods of family planning are using one of them is Today method of family planning in which cervix secretion is noticing for two consecutive days, if there is cervical secretion then unprotected sex may be avoided. Other methods of family planning include oral contraceptives, injectable, IUCD, male condom. Objectives: Purpose –To assess the prevalence of family planning methods in married women at THQ Hospital shabqadr Methodology: Study Design- Descriptive cross sectional survey. Sampling Techniques- convenient sampling technique. Sample Size- Total 273 participants were selected for the study and sample size was calculated through OpenEpi on the basis of 23% proportion of family planning in KPK with 95 % of confidence interval and 5% margin of error, Results: Participants were inform from different sources, 35.1% got information about family planning from government hospital, while 5.9% source was their friend health worker also use as source of information for 56.4% and 2.6% subjects were informed by their relatives, the results showing in the figure. Different methods were use 23.4% IUCD, Injectables,13.9%, implant 10.3%, pills, 19% Condom. Conclusion: Family planning is very important in this over populated world especially in fast growing populated country Pakistan. Different sources working on awareness about family planning, lady health workers are more involve in the awareness which is highly appreciated. Oral contraceptive pills are abundantly using method in this study. More awareness is required about side effect and contraindication of this method.